2021
DOI: 10.1111/radm.12470
|View full text |Cite
|
Sign up to set email alerts
|

Open Covid‐19: Organizing an extreme crowdsourcing campaign to tackle grand challenges

Abstract: This article presents an extreme crowdsourcing case to tackle grand challenges such as Covid‐19. Researchers became more interested in crowds’ involvement to deal with grand challenges and scholars reported the use of crowdsourcing in producing innovative solutions to solve these challenges. Driven by recent calls for more research to examine forms of socially motivated interaction options in order to support crowds in dealing with these ill‐defined problems, this research conducts a qualitative study of how a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 54 publications
(94 reference statements)
0
22
0
Order By: Relevance
“…The implementation of a crowd-based, open peer-review system followed the need to support two nascent community efforts, first by allocating volunteers to projects in the COVID relief charity Helpful Engineering (18), then by allocating funding to projects in the JOGL “OpenCOVID19” initiative (17). The method was developed as an open access grant review and funding allocation system, meaning that it was open to anyone willing to review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of a crowd-based, open peer-review system followed the need to support two nascent community efforts, first by allocating volunteers to projects in the COVID relief charity Helpful Engineering (18), then by allocating funding to projects in the JOGL “OpenCOVID19” initiative (17). The method was developed as an open access grant review and funding allocation system, meaning that it was open to anyone willing to review.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests there is a potential for a new, more agile route for community-driven grant allocation bypassing pre-selected grant panels that handle funds and introduce barriers (8), and relying instead on peer applicants to handle a large-scale application process in a short timescale. In this study, we present the design, implementation, and results of a community-driven, open peer-review system to support two open research communities during the COVID pandemic across seven selection rounds ( Fig1 ): the “OpenCOVID19” initiative from Just One Giant Lab (JOGL) (14,17) and the COVID relief charity Helpful Engineering (18). We show that this system is robust (unaffected by reviewer removal), agile (fast timeline), iterative (covering multiple grant rounds), decentralised (driven by the community), and scalable.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars almost always emphasize that organizing is a central method (i.e., Ferraro, Etzion, and Gehman, 2015;George et al, 2016;Jarzabkowski, Le ˆ, and Balogun, 2019;Howard-Grenville, 2021). Research has shown how risky entrepreneurial ventures have been organized to alleviate poverty in developing nations (Dorado, 2013), that people can be organized through national partnerships to address climate change (Burke and Wolf, 2020), and that organizing through crowdsourcing campaigns can support the development of low-cost solutions for addressing the COVID-19 pandemic (Kokshagina, 2021). But while researchers have touted ''coordinating'' and ''collaborating'' (George et al, 2016) as strategies for addressing grand challenges, there are emotional realities of struggling to do so (see de Rond and Lok, 2016).…”
Section: Grand Challengesmentioning
confidence: 99%
“…For instance, the case of the community-based digital contact tracing in Wuhan (Boeing and Wang, 2021), showed how the platform and the community could mediate between the needs of the government of enforcing a system to monitor the spreading of COVID-19 and the needs of citizens to feel less exposed and that their information was managed ethically. Knowledge management and project management capabilities as well as communitybuilding themes emerged across the SI, both illustrated in the description and role of hackathons and crowdsourcing (Bertello et al, 2021;Kokshagina, 2021;Vermicelli et al, 2021) and within projects across consortia (Di Guardo et al, 2021;von Behr et al, 2021). Other coordination mechanisms were proposed through the uses of tools: Guderian et al (2021) reminds us of how patent analytics could be applied to detect where key competencies reside, while Whal et al ( 2021) promote adoption of data mining tools to analyse the landscape of key problems that need solving in a pandemic.…”
Section: Bottom Up or Top Down? The Importance Of Coordination Capabi...mentioning
confidence: 99%